KECEMASAN BERBAHASA INGGRIS PADA MAHASISWA BAHASA INGRIS TAHUN KEDUA FKIP UNIVERSITAS RIAU - Marlianti, Marlianti; Jismulatif, Jismulatif; Dahnilsyah, Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aimedto determine the level of anxiety of English students in speaking English. The populations in this study werethe second year English Faculty FKIP Riau University students. Onthe implementation,the researcher used simple random sampling technique (n = 30). The data were collected by distributing a set of questionnaires adapted from FLCAS (Foreign Language Anxiety classroom Anxiety Scale) and designed by Horwitz et al., 1986. Based on the data analysis, it couldbe seen that their anxiety level is in the moderate category, with an average of 2 , 78. Specifically, the data analysis also showedthe level of student anxiety in each of its components, with an average at a moderate level with an average score of 2.80. This shows that their level ofEnglish anxiety is in the moderate.KeyWord: Foreign Language Anxiety, Component Anxiety